2016
DOI: 10.3390/nu8100634
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Milk Consumption and Vitamin B2 and Β12 Derived from Milk with Fitness, Anthropometric and Biochemical Indices in Children. The Healthy Growth Study

Abstract: The benefits of dairy consumption seem to extend beyond its significant contribution to ensuring nutrient intake adequacy as indicated by the favourable associations with several health outcomes reported by different studies. The aims of the present study were to examine the associations of milk consumption with fitness, anthropometric and biochemical indices in children and further explore whether the observed associations are attributed to vitamins B2 and B12 derived from milk. A representative subsample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Of the 4145 children who were eligible to participate, 2656 were enrolled in the study (64.1% response) after the parents signed consent on behalf of the children. Detailed methodology has been published elsewhere [ 16 ]. Of these 2656 children, a subsample of 1338 children who had full data on both the independent and dependent variable were used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Of the 4145 children who were eligible to participate, 2656 were enrolled in the study (64.1% response) after the parents signed consent on behalf of the children. Detailed methodology has been published elsewhere [ 16 ]. Of these 2656 children, a subsample of 1338 children who had full data on both the independent and dependent variable were used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Three studies have examined the associations between dairy consumption and cardiorespiratory fitness [58,59,60]. A significant positive association has been reported between dairy consumption and cardiorespiratory fitness in 9–13 year-old Greeks, 12–17 year-old Europeans, and 14–19 year-old Brazilians [58,59,60]. Dairy products are rich sources of essential amino acids, vitamins (e.g., B2 and B12), and minerals (e.g., zinc and calcium) [61,62].…”
Section: Physical Fitnessmentioning
confidence: 99%
“…In addition, four studies have determined the association between individual foods and muscular strength [60,75,76,77]. No significant associations were found between daily milk consumption (β = −0.02 kg, p = 0.782) [60], frequency of fruit and vegetable intake (β = 0.012 kg, p = 0.155) [75], and amount of daily fruit and vegetable consumption [76] with handgrip strength in 9–13 year-old Greeks, 6–11 year-old Europeans, and 5–18 year-old Americans, respectively. Only a study by Neville et al [77] found that Irish girls (12 and 15 years) in the lowest tertile of fruit and vegetable consumption had significantly lower handgrip strength than those in the highest tertile of fruit and vegetable consumption (β = −0.75 kg, 95% CI = −1.35, −0.15 kg).…”
Section: Physical Fitnessmentioning
confidence: 99%
“…Milk and dairy products, in particular, have received special interest since they are widely consumed by children, as they are rich in several nutrients that are essential for growth and maintenance of a healthy life (MOSCHONIS et al, 2016) and also provide immunological protection (LARSSON et al, 2015;LAMARCHE et al, 2016).…”
Section: Introductionmentioning
confidence: 99%